Exploration of the Process of Making Batik Sendang Duwur as a Physics Teaching Material on Temperature and Heat - Fatihatun Nikmah; Nadi Suprapto; Binar Kurnia Prahani; Utama Alan Deta (Universitas Lambung Mangkurat, 2023)
This study explores the concept of physics in local potential, namely hand-drawn batik, by integrating indigenous science with scientific science. The discussion will be related to the physical concepts of temperature and heat transfer at each step or process of making batik, such as heating wax to write batik patterns, dyeing batik cloth, removing batik wax, and drying batik. This research is qualitative research with interview and observation techniques on batik craftsmen in Sendang Duwur Village, Paciran Lamongan. The data analysis technique used refers to the Miles and Huberman model. This study made observations, followed by an exploration of the physics concept of the batik process directly and supported by existing theories. The results of this study there are concepts of physics applied in making Batik Sendang Duwur, especially temperature and heat physics.